Advances in Location-Based Services 8th International Symposium on Location-Based Services, Vienna 2011 - Gartner, Georg.; Gartner, Georg.; Ortag, Felix.; Ortag, Felix. (Lecture Notes in Geoinformation and Cartography,, 2012)
This book gives a general picture of research-driven activities related to location and map-based services. The interdisciplinary character of the topic leads to a variety of contributions with backgrounds from academia to business and from computer science to geodesy. While cartography is aiming at efficient communication of spatial information, the development and availability of technologies like mobile networking, mobile devices or short-range sensors lead to interesting new possibilities of achieving this aim. By trying to make use of the available technologies, a variety of related disciplines looks specifically at user-centered and context-aware system development, especially in wayfinding and navigation systems.